(untitled) (Archives of Mechanics - Test, 2003)
The two-dimensional flow problem of a third order incompressible fluid past an infinite porous plate is discussed when the suction velocity normal to the plate, as well as the the external flow velocity, varies periodically with time. The governing partial differential equation is of third order and nonlinear. Analytic solution is obtained using the series method. Expressions for the velocity and the skin friction have been obtained in a dimensionless form. The results of viscous and second order fluids can be recovered as special cases of this problem. Finally, several graphs are plotted and discussed.